The Correlational Analysis of Aerobic Gymnastics and The Students' Physical Fitness, and Their Learning Motivation at STIKES Hang Tuah Surabaya - Lela Nurlela; Dhian Satya Rahmawati; Merina Widyastuti; Sukma Ayu Candra Kirana; Nur Chabibah; Choiririn Erick Gumilan; Faisal Amir (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2023)
Background: Health and intelligence are two important things to increase knowledge in education. The physical health will support psychology health to increase motivation. The aims of the research are to correlational analysis on aerobic gymnastics the students’ physical fitness and their learning motivation at STIKES Hang Tuah Surabaya. Method: the research design is correlational analysis with cross sectional approach. The number of population are 58 with a sample of 50 was taken by simple random sampling. Univariate data were analyzed usingg the frequency distribution. Bivariate data were tested by using spearman rank with alpha <0.05. Results: The statistical test with spearman ranks showed a significant relationship between the aerobic gymnastic and the students’s physical fitness with p value of 0.022. There is a significant relationship between the aerobic gymnastic and their learning motivation with a p value of 0.027 which is smaller than alpha 0.05. Conclussion: The aerobic gymnastic is able to optimize the suplly, intake and oxygen use in forming ATP which has an impact on students’s physical fitness and their learning motivation.